2021
DOI: 10.1021/acsomega.1c00766
|View full text |Cite
|
Sign up to set email alerts
|

A General Route of Using Lignite Depolymerized Derivatives for Catalyst Construction: Insights into the Effects of the Derivative Structures and Solvents

Abstract: Depolymerization is an emerging and promising route for the value-added utilization of low-rank coal (LRC) resources, and how to use the complex depolymerized mixtures efficiently is of great importance for this route. In this work, we designed the rational route of using depolymerized mixtures from lignite via ruthenium ion-catalyzed oxidation (RICO) depolymerization directly without complex separation to construct a Zr-based hydrogenation catalyst. The prepared catalyst was applied int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…A very recent report in 2021 from China describes the use of Zr-HA and Cu-HA catalysts (Hao et al, 2021). The former zirconium-based compound has been demonstrated as a suitable reusable catalyst for carrying out the reduction of organic substrates, while the latter copper-containing compound is useful for oxidation.…”
Section: Zr-ha and Cu-ha Catalysts For Reduction And Oxidation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent report in 2021 from China describes the use of Zr-HA and Cu-HA catalysts (Hao et al, 2021). The former zirconium-based compound has been demonstrated as a suitable reusable catalyst for carrying out the reduction of organic substrates, while the latter copper-containing compound is useful for oxidation.…”
Section: Zr-ha and Cu-ha Catalysts For Reduction And Oxidation Processesmentioning
confidence: 99%
“…These include making humic substance-based solar cells (Rohit et al, 2016). Based on reverse polymerization of humic substances, zirconium-humic acid (Zr-HA) and copper-humic acid (Cu-HA) catalysts, respectively for reduction and oxidation processes, have been developed recently (Hao et al, 2021) 1 . However, in these pandemic times, what catches attention most is the antiviral activity, in particular the reported anti-HIV-AIDS activity of humic substances (Zhernov et al, 2020), which has been shown to be superior to Himalayan Shilajit, an immune booster available from Dabur Co., Ghaziabad, India 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Meerwein–Ponndorf–Verley (MPV) reduction, which employs suitable alcohols as the hydrogen resources, is a feasible strategy to achieve chemoselective hydrogenation of carbonyl groups. Generally, MPV reduction of carbonyl groups can be promoted by Al-, Sn-, , Hf-, or Zr-based catalysts, which have lower hydrogenation activity on other reducible groups, thus making MPV reduction highly selective on carbonyl groups. Among various catalysts, Zr-based catalysts (i.e., inorganic materials and organic–inorganic hybrids) are the most used class for MPV reduction of carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ion-organic ligand hybrid MPV catalysts are commonly used for the MPV reduction of furfural. The Zr-based catalysts such as UiO-66 (Qiu et al, 2020), Zr-DM (Hao et al, 2021), Zr-HAs (Sha et al, 2017), Zr-RSL (Hao et al, 2019) and Zr/Fe (Gu et al, 2020) showed good catalytic activity in the catalytic hydrogenation reaction using alcohols as hydrogen donors. The selection of ligands is important for the construction of metal ion-organic ligand hybrid MPV catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the pure organic carboxylic acids, the natural macromolecules rich in organic carboxylic groups are also used in the construction of the MPV catalysts. In our previous work, the lignite derived humic acids and even lignite were used to construct Zr-containing MPV catalysts, and the prepared catalysts were proved to be highly efficient for the MPV reduction of various carbonyl compounds (Sha et al, 2017;Hao et al, 2019;Hao et al, 2021). Natural compounds rich in acidic carboxyl functional groups are natural functional molecules widely existing in nature (Luo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%